Comparative study of the toxic effects of Chrysaora quinquecirrha (Cnidaria: Scyphozoa) and Chironex fleckeri (Cnidaria: Cubozoa) venoms using cell-based assays. (November 2015) - Ponce, Dalia; Brinkman, Diane L.; Luna-Ramírez, Karen; Wright, Christine E.; Dorantes-Aranda, Juan José
Abstract: The venoms of jellyfish cause toxic effects in diverse biological systems that can trigger local and systemic reactions. In this study, the cytotoxic and cytolytic effects of Chrysaora quinquecirrha and Chironex fleckeri venoms were assessed and compared using three in vitro assays. Venoms from both species were cytotoxic to fish gill cells and rat cardiomyocytes, and cytolytic in sheep erythrocytes. Both venoms decreased cell viability in a concentration-dependent manner; however, the greatest difference in venom potencies was observed in the fish gill cell line, wherein C. fleckeri was 12.2- ( P = 0.0005) and 35.7-fold ( P < 0.0001) more potently cytotoxic than C. quinquecirrha venom with 30 min and 120 min cell exposure periods, respectively. Gill cells and rat cardiomyocytes exposed to venoms showed morphological changes characterised by cell shrinkage, clumping and detachment. The cytotoxic effects of venoms may be caused by a group of toxic proteins that have been previously identified in C. fleckeri and other cubozoan jellyfish species. In this study, proteins homologous to CfTX-1 and CfTX-2 toxins from C. fleckeri and CqTX-A toxin from Chironex yamaguchii were identified in C. quinquecirrha venom using tandem mass spectrometry. The presence and relative abundance of these proteins may explain the differences in venom potency between cubozoan and scyphozoan jellyfish and may reflect their importance in the action of venoms. Highlights: Jellyfish venoms were cytotoxic to gill cells and rat cardiomyocytes, decreasing cell viability by 100% at 30 and 120 min. Jellyfish venoms were haemolytic for sheep erythrocytes ( Chironex fleckeri HU50 = 27.4 μg mL −1 ). C. fleckeri venom was more potently cytotoxic to gill cells and haemolytic to sheep erythrocytes than Chrysaora quinquecirrha venom. Proteins homologous to jellyfish toxins CfTX-1, CfTX-2 and CqTX-A were identified in the venom of C. quinquecirrha.